TRANSLATION STRATEGIES OF IDIOMATIC EXPRESSIONS IN "AN ABUNDANCE OF KATHERINES": English - Wibowo, Selvinatasya; Supardi, Moh. Supardi (BASIS (Bahasa dan Sastra Inggris), 2024)
This study aims at investigating the translation strategies and the equivalence of idiomatic expressions in the "An Abundance of Katherines". The study employs a descriptive qualitative approach. The data source of the study was gathered from the novel "An Abundance of Katherines" and its translation. The data were collected randomly from the source text (ST) and target text (TT). The collected data were analyzed qualitatively based on idiomatic translation strategies, for instance paraphrasing the idiomatic expressions that maintain similar meanings through dissimilar styles or forms as the most frequently strategy employed by the translator. The results of this study indicate that the idiom translation strategy applied by the translator uses the idiom translation strategy with paraphrasing. This seems to be based on the idea that the translator tends to preserve the equivalence in meaning between the source and target languages, for example idioms are translated into non-idioms, idioms with idioms, etc. This research concludes that the translator seems to apply her own strategies by paraphrasing the source text idioms more often into non-idioms in the target text in order to obtain equivalence in meaning and culture. In general, the strategies of translation carried out by the translator can be categorized as acceptance translation and equivalence in terms of meaning and culture. Therefore, this study suggests for translators who wish to translate idioms from English into Indonesian should not be restricted on one theory of translation, but must be more flexible by considering the contextual and cultural factors.